Image Classification Using Bag of Visual Words (BoVW) - Karim, Abdul Amir Abdullah; Sameer, Rafal Ali (Al-Nahrain Journal of Science, 2018)
In this paper two main stages for image classification has been presented. Training stage consists of collecting images of interest, and apply BOVW on these images (features extraction and description using SIFT, and vocabulary generation), while testing stage classifies a new unlabeled image using nearest neighbor classification method for features descriptor. Supervised bag of visual words gives good result that are present clearly in the experimental part where unlabeled images are classified although small number of images are used in the training process.